2013
DOI: 10.1177/1932202x13476289
|View full text |Cite
|
Sign up to set email alerts
|

Early College and Dual Enrollment Challenges

Abstract: In recent years, some school reformers have come to see early college and dual enrollment as mechanisms for increasing the academic engagement and performance of a range of students beyond those exhibiting high academic achievement or ability. Despite purported benefits, research on the dynamics of such programs is limited. This case study adds to the relevant literature by using semistructured interviews with key participants to investigate the cross-institutional dynamics enabling and constraining the early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…The one dual-credit article suggested that low-income students who participated in dual-credit programs at community colleges were more likely to enroll and complete college at statistically and practically significant levels. This is consistent with previous research that has found that dual-credit programs have supported low-income students in extending students’ perspectives (Howley, Howley, Howley, & Duncan, 2013) and accessing and succeeding in college (Allen & Dadgar, 2012; An, 2013).…”
Section: Resultssupporting
confidence: 93%
“…The one dual-credit article suggested that low-income students who participated in dual-credit programs at community colleges were more likely to enroll and complete college at statistically and practically significant levels. This is consistent with previous research that has found that dual-credit programs have supported low-income students in extending students’ perspectives (Howley, Howley, Howley, & Duncan, 2013) and accessing and succeeding in college (Allen & Dadgar, 2012; An, 2013).…”
Section: Resultssupporting
confidence: 93%
“…However, successfully implementing a dual enrollment program likely faces more impediments than starting an AP program, and it is important that factors such as funding arrangements, communication between levels, and community awareness are addressed (Howley, Howley, Howley, & Duncan, 2013; Stephenson, 2014). Furthermore, some rural districts that are unsuitable for AP programs may also lack a nearby tertiary institution with which to establish a dual enrollment program.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has reported that, on average, ECHSs "serve students who are similar to the student populations in their districts in terms of eligibility for freeand reduced-price lunch and race/ethnicity" (Edmunds et al, 2017, p. 304). Parent education levels of students also vary across ECHSs (Berger et al, 2014;Cravey, 2013;Edmunds et al, 2012;Howley et al, 2013;Muñoz et al, 2014). With respect to academics, some studies have found that entering ECHS students demonstrate significantly higher achievement, on average, compared to their non-ECHS peers (Berger et al, 2014;Edmunds et al, 2017).…”
Section: Echs Admission and Demographicsmentioning
confidence: 99%